Pengaruh Kualitas Pelayanan Dan Persepsi Pasien Terhadap Kepuasan Pasien Rawat Jalan Di Rumah Sakit Muji Rahayu Surabaya - Lia Kartika Devi; Nur Aini Anisa; Nur Farida (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This research employs an associative research type with a quantitative approach. The study is motivated by the objective to analyze the Service Quality (X1) and Patient Perception (X2) on Outpatient Patient Satisfaction (Y) at Muji Rahayu Hospital, Surabaya, involving 151 respondents. The sampling technique used in this research is purposive sampling. Data analysis is conducted using statistics with the assistance of SPSS software. Based on the results of the data analysis using the t-test, it is found that partially, the variables Service Quality (X1) and Patient Perception (X2) have a significant influence on Outpatien Patient Satisfaction (Y) at Muji Rahayu Hospital, Surabaya. Then, based on the results of the data analysis using the F-test, it is revealed that simultaneously, the variables Service Quality (X1) and Patient Perception (X2) have a significant influence on Outpatient Patient Satisfaction (Y) at Muji Rahayu Hospital, Surabaya.